EMOTIONAL REGULATION STRATEGIES AMONG EFL MASTER’S STUDENTS AT SANATA DHARMA UNIVERSITY: NAVIGATING ACADEMIC CHALLENGES AND STRESS - Edeltrudis Patrisia Soge; Simron Krisnuarjati Hindom; Galuh Wuryaningtyas; Concilianus Laos Mbato (Widya Mandala Surabaya Catholic University, 2025)
ABSTRACT Emotions are physiological states that significantly influence the learning process. Students must regulate their emotions when confronted with challenges in higher education. This study addresses the research questions: 1.) How do Masters students regulate their emotions in academic life? and 2.) What are the perceived effects of emotion regulation in their academic life? This study used an explanatory sequential mixed method with 21 participants from the first semester of the English education master's program at Sanata Dharma University batch 2024. Observation, questionnaire, and interview were used to collect the data. This study used the process of recognition, coding, data reduction, data display, and triangulation techniques. The results showed that students had varied perspectives of emotional regulation towards their academic life. It was influenced by their thoughts, environment, and personal jobs. They faced challenges such as heavy workloads, time constraints, nervousness, stress, anxiety, and personal issues. To overcome this, the students seek help from friends, family, and lecturers, choose relaxing activities, and shift their mindsets. It was found that students' emotional regulation varied depending on their academic situation during the semester. On the other hand, students perceived the effect of emotional regulation, which is knowing themselves better, boosted confidence, better understanding of the materials, improved time management, and healthy relationships. This research highlights the importance of emotional regulation for first-semester master's students adapting to a new environment, aiding their academic success.